Feu le régime d’accumulation tiré par la finance - Robert Boyer (Revue de la Régulation)
Financial liberalization has triggered a series of financial innovations that seemed to define, at least transitorily and for the US and UK, an unprecedented consumer credit-led accumulation regime. But financial innovations diffuse, quite quickly, since they are intangible and have major consequences for macroeconomic stability due to various externalities. Such a process took place for the securitization of mortgage credit. Therefore, the present crisis is not only that of over-accumulation in the real estate sector. Its severity and rapid international diffusion derive from the systemic collapse of financial valuation. It is the direct consequence of the anti-division of labour within the financial sector that has permanently externalized and underestimated the risk by hiding it into more and more complex and esoteric products. This lost informational content of financial pricing leads to the freeze of credit first within financial institutions and then households and ultimately firms. Within the taxonomy of “regulation” theory, this is a structural/major crisis, the overcoming of which is radically uncertain. The social control of financial innovation is one of the issues at stake.